Explaining the Media's Framing of Renewable Energies: An International Comparison - Rochyadi-Reetz, Mira; Arlt, Dorothee; Wolling, Jens; Bräuer, Marco (Frontiers in Environmental Science, 2019)
The use of renewable energies has been rapidly expanding worldwide; however, in numerous countries this has resulted in public controversy. Building upon Entman’s framing concept, a quantitative content analysis was conducted to examine the media’s framing of renewable energies in 11 countries between 2010 and 2012. To explain the observed differences in media coverage, we considered national structural conditions. Furthermore, we investigated whether media framing changed after an external shock, the Fukushima accident. The findings show that renewable energies were covered through three different frames, (1) the first highlighting economic and technological problems, (2) the second focusing on environmental and social problems and (3) the third considering positive aspects of the technologies. To some extent, the occurrence of these frames is influenced by the national structural conditions. The study revealed that the Fukushima accident did not cause the expected changes in framing.